Quick Survey of Availability and Sale of Controlled Cloth in 32 Urban Towns - Planning Commission (Planning Commission, 1978)
The Programme Evaluation Organization has been observing the trends in prices of essential articles in the retail markets of Delhi/ New Delhi, since September, 1975. Controlled cloth is one of the articles taken up under the Survey. On the basis of the observations in the first two months, a Note was prepared on the prices and availability of controlled cloth for these markets and was sent to the Ministry of Commerce for information. On receipt of this review, the Ministry of Commerce suggested that the PEO may conduct a Survey of other major towns also. On this request, PEO launched in March 1976.
Programme Evaluation Organisation Planning Commission Government of India